1977
DOI: 10.1192/bjp.131.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Marital Stability Following the Birth of a Child with Spina Bifida

Abstract: The matrimonial stability of 142 families where a child with neural tube malformation (mostly spina bifida) was born between 1964 and 1966, including 56 families with a surviving spina bifida child, was examined in January 1976. The divorce rate for families with a surviving child was found to be nine times higher than that for the local population and three times higher than for families experiencing bereavement of their spina bifida child. Marriages which followed a pre-nuptial conception resulting in a spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2
2

Year Published

1981
1981
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 4 publications
1
12
2
2
Order By: Relevance
“…A few previous studies which involved small numbers of families also reported a higher frequency of divorce among parents of children with spina bifida (Kolin et al 1971;Martin 1975;Tew et al 1977). The frequency of divorce was three times higher among caregivers of children with the highest lesion levels than among those with the lowest level lesions and three times higher among those whose children could not walk as among those whose children had no major mobility limitations, but we cannot exclude the probability that these associations might be due to chance.…”
Section: Discussioncontrasting
confidence: 41%
“…A few previous studies which involved small numbers of families also reported a higher frequency of divorce among parents of children with spina bifida (Kolin et al 1971;Martin 1975;Tew et al 1977). The frequency of divorce was three times higher among caregivers of children with the highest lesion levels than among those with the lowest level lesions and three times higher among those whose children could not walk as among those whose children had no major mobility limitations, but we cannot exclude the probability that these associations might be due to chance.…”
Section: Discussioncontrasting
confidence: 41%
“…Lower marital integration has been found in families with a mentally retarded child living at home (Farber, 1959) and in families with various kinds of handicapped children (Friedrich & Friedrich, 1981). A higher than average rate of marital breakdown was reported for parents of infants with Down syndrome (Gath, 1977) and parents of children with spina bifida (Tew, 1974;Tew & Laurence, 1973;Tew, Laurence, Payne, & Rawnsley, 1977). Psychological dysfunctioning and psychiatric problems were found frequently in parents with mentally retarded children (Schonell & Watts, 1957) and with physically handicapped and chronically ill children (Dorner, 1973;McAndrew, 1976).…”
Section: Stress and Adaptation In Parents Of Youngmentioning
confidence: 92%
“…Sie ist eine wichtige Ressource für das Gedeihen und Wachsen eines von chronischer Erkrankung betroffenen Kindes. Leider scheitern Eltern jedoch nicht selten bei der Bewälti-gung dieser Belastung [18,19,20]. Gesunde Geschwisterkinder erleben hilflose Eltern, werden mit medizinischen, oft auch für Erwachsene unverständlichen Sachverhalten konfrontiert und ebenso häufig dazu angehalten, darüber nicht zu sprechen.…”
Section: Rolle Der Familieunclassified